2008
DOI: 10.1300/j394v05n01_10
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practice in Human Service Organizations

Abstract: Evidence-based practice (EBP) involves the integration of the expertise of individual practitioners with the best available evidence within the context of values and expectations of clients. Little is known about the implementation of evidence-based practice in the human services. This article is based on a comprehensive search of the literature related to the organizational factors needed to introduce EBP into a human service agency, tools for assessing organizational readiness for EBP, and lessons learned fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Several implementation frameworks include the measurement of organizational factors such as the implementation climate, learning culture, or leadership yet offer little practical guidance for these types of interventions (e.g., Aarons & Sommerfeld, 2012;Austin & Claassen, 2008;Beidas et al, 2013). The PACE program contributes to the few efforts among community-based mental health agencies that integrate organizational level interventions with the implementation process (e.g., Barwick et al, 2011;Williams, Glisson, Hemmelgarn, & Green, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several implementation frameworks include the measurement of organizational factors such as the implementation climate, learning culture, or leadership yet offer little practical guidance for these types of interventions (e.g., Aarons & Sommerfeld, 2012;Austin & Claassen, 2008;Beidas et al, 2013). The PACE program contributes to the few efforts among community-based mental health agencies that integrate organizational level interventions with the implementation process (e.g., Barwick et al, 2011;Williams, Glisson, Hemmelgarn, & Green, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The CARI consists of 40 items across eight domains: organizational capacity, organizational climate/culture, staff capacity, implementation plan, system level capacity, functional considerations, senior leadership, and training. It was adapted from a tool proposed by Austin and Claassen (2008) which consisted of 20 items along four domains on a 4-point scale (1 = Not even close, 2 = Some way to go, 3 = Nearly there, 4 = We're there).…”
Section: Procedures and Sources Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on implementation is growing and has been very instructive in responding to these challenges. Austin and Claassen (2008) conducted a comprehensive review of literature addressing the organizational factors needed to introduce EBP into human service agencies and concluded that ''EBP requires special attention to the processes of organizational change, the understanding of organizational culture, and the specialized expertise to promote the successful dissemination and utilization of research'' (p. 274). These findings are also echoed in the analysis done by RiP and led to the development of two excellent resources: Firm Foundations: A Practical Guide to Organizational Support for the Use of Research Evidence (Barratt & Hodson, 2006) and Leading EvidenceInformed Practice: A Handbook (Hodson & Cooke, 2007).…”
Section: Critical Factors In Implementationmentioning
confidence: 99%
“…Knowledge and clinical experience are the most important factors in clinical decision making [2]. There is a need to develop the body of knowledge about how to implement evidence-based practice in decision making on micro-and macro-levels in community nursing care [3].…”
Section: Introductionmentioning
confidence: 99%